Reovirus Activates a Caspase-Independent Cell Death Pathway - Angela K. Berger; Pranav Danthi (2013)
Virus-induced apoptosis is thought to be the primary mechanism of cell death following reovirus infection. Induction of cell death following reovirus infection is initiated by the incoming viral capsid proteins during cell entry and occurs via NF-κB-dependent activation of classical apoptotic pathways. Prototype reovirus strain T3D displays a higher cell-killing potential than strain T1L. To investigate how signaling pathways initiated by T3D and T1L differ, we methodically analyzed cell death pathways activated by these two viruses in L929 cells. We found that T3D activates NF-κB, initiator caspases, and effector caspases to a significantly greater extent than T1L. Surprisingly, blockade of NF-κB or caspases did not affect T3D-induced cell death. Cell death following T3D infection resulted in a reduction in cellular ATP levels and was sensitive to inhibition of the kinase activity of receptor interacting protein 1 (RIP1). Furthermore, membranes of T3D-infected cells were compromised. Based on the dispensability of caspases, a requirement for RIP1 kinase function, and the physiological status of infected cells, we conclude that reovirus can also induce an alternate, necrotic form of cell death described as necroptosis. We also found that induction of necroptosis requires synthesis of viral RNA or proteins, a step distinct from that necessary for the induction of apoptosis. Thus, our studies reveal that two different events in the reovirus replication cycle can injure host cells by distinct mechanisms.Virus-induced cell death is a determinant of pathogenesis. Mammalian reovirus is a versatile experimental model for identifying viral and host intermediaries that contribute to cell death and for examining how these factors influence viral disease. In this study, we identified that in addition to apoptosis, a regulated form of cell death, reovirus is capable of inducing an alternate form of controlled cell death known as necroptosis. Death by this pathway perturbs the integrity of host membranes and likely triggers inflammation. We also found that apoptosis and necroptosis following viral infection are activated by distinct mechanisms. Our results suggest that host cells can detect different stages of viral infection and attempt to limit viral replication through different forms of cellular suicide. While these death responses may aid in curbing viral spread, they can also exacerbate tissue injury and disease following infection.